Embodiment, Empathic Perception, and Spiritual Ontologies in Q'eqchi’ Maya Healing: An Ethnographic Exploration - Hatala, Andrew R. (Ethos, 2020)
Social science research and theory suggests that perception can be viewed as an embodied process of social and cultural mediation. This embodied view of perception involves deep connections between the mind and body, as well as the larger social context. Previous research with Maya communities has outlined how aspects of subject and object, or self and other, can be bridged through forms of social connectedness with the family or community. This ethnographic work with Q'eqchi’ Maya healers in southern Belize details embodied and sensual aspects of therapeutic encounters, including aspects of healers embodied modes of perception or “signs” during pulse reading, manual manipulation, dreams, and prayer that mesh together and span across worlds of flesh and spirit. These embodied forms of somatic knowledge further allow us to reflect on the notions of “empathy” in Q'eqchi’ clinical encounters, challenging cognitive biases and boundaries of patients, healers, and spiritual worlds. Exploring an ontological shift away from mere material bodies and social actors opens new directions for embodiment literature and a query of spiritual ontologies. Methodological and theoretical tools to critique a spiritual/material dualism and re-vision embodiment practices of therapeutic engagement, including their clinical significations, representations, and cultural meanings, are also explored.